Uma proposta didática sobre plantas medicinais nos anos iniciais do ensino fundamental na perspectiva ciência-tecnologia-sociedade - Maciel, Flávia Rossi (Universidade Federal de São Carlos, 2016)
This research originated from issues related to scientific literacy, aimed to analyze the potential and limitations of the study on medicinal plants from the CTS approach (Science- Technology-Society). Science education according to this perspective establishes relationships between scientific knowledge, technological development and social reality in order to encourage responsible decision making. Therefore, the research involved the participation of twenty students in a class of 3rd grade of elementary school of a municipal school in the interior of São Paulo and was developed through activities with CTS character, interdisciplinary and contextual. We used as instruments to collect data daily researcher, the written record and represented by designs of the students, the audio recording of his speeches and photographs. For the data analysis, established as criteria the Structuring Axes of Scientific Literacy proposed by Sasseron and Carvalho (2011) and we adapted. As a result, we identified indicative aspects of the process of initiation to scientific literacy. Among them we highlight the construction of relevant knowledge to the context of life of students and applicable to everyday situations, awareness of responsible actions through analysis and reflections on the new information and evidence of understanding of the relationship between science, technology, society and its implications. The study also highlighted the importance of attentive and active role of the teacher during the development of the activities and pointed out limitations regarding the conduct of discursive activity in science classes and difficulty in articulating the opinions of students and science concepts. Finally, we believe that this research could contribute to the practice of teachers working in the early years of elementary school to consider training as a continuum.
Keywords: Alfabetização científica; Ciência, Tecnologia e Sociedade (CTS); Plantas medicinais; Anos iniciais do ensino fundamental; Scientific Literacy; Science; Technology and Society (STS); Medicinal plants; Years Elementary School Initials; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO